Prevalence and associated risk factors of gout among patients at Khyber Teaching Hospital Peshawar: A cross-sectional study - Khan, Inam Ullah; Khan, Moheb Ullah; Khan, Shameem; Ullah, Ahmad; Khan, Muhammad Waqas; Ullah, Wahid (Svāsthya: Trends in General Medicine and Public Health, 2024)
Hyperuricemia and gout represent significant global public health challenges with varying prevalence rates across populations. This study aimed to investigate the prevalence and associated risk factors for gout among patients at the Khyber Teaching Hospital, Peshawar, Pakistan. This cross-sectional analytical study was conducted from January to March 2024 and involved 100 patients (57% female, 43% male) aged 18–65 years. Participants were recruited via systematic random sampling from the orthopedic department. Data collection included demographic information, anthropometric measurements, medical history, and serum uric acid levels, which were analyzed via the uricase enzymatic colorimetric method. 93% of the patients were between 21 and 60 years old, with 54% reporting a family history of gout. Notably, 95% of the participants presented elevated uric acid levels (>6.8 mg/dL in men, >6.0 mg/dL in women), with 40% falling within the 7.1–8.0 mg/dL range. The major comorbidities included hypertension (72%), thyroid problems (45%), and kidney disease (34%). Protein-rich diet consumption was reported by 84% of the participants, whereas alcohol consumption was reported by 17%. The general health assessment classified 65% of the participants as unhealthy. The findings indicate a greater prevalence of gout among females in this population, contradicting traditional patterns, along with significant associations with comorbidities and dietary factors. This study highlights the need for sex-specific screening protocols and comprehensive management approaches that address both primary gout symptoms and associated conditions. These results emphasize the importance of early intervention and lifestyle modification strategies in gout management within the South Asian.